Elucidating the influence of volatile compounds on aroma profiles across peach (Prunus persica L.) cultivars and offspring exhibiting diverse flesh colors - Yuanyuan Zhang; Binbin Zhang; Zhixiang Cai; Zhijun Shen; Mingliang Yu; Ruijuan Ma (Current Research in Food Science)
Yellow- and white-fleshed peach fruits are favored for their diverse flesh colors. While carotenoid accumulation primarily dictates flesh color differences, the influence of volatile compounds on their aromas remains largely unexplored. Here, multiple analytical methods including odor importance assessment, hierarchical clustering, and aroma characterization analysis were employed to investigate volatile compositions and aroma characteristics of the two types of peach, as well as the offspring with identical parentage. Dihydro-β-ionone was the sole volatile exhibiting content and odor importance disparities between the two types of peach, and in descendant cultivars such volatiles encompassed theaspirane additionally. Respectively 16 and 30 important volatiles were identified in the two peach types and in the offspring cultivars, and subsequently overview of their aroma characteristics was obtained from a graphical perspective. The two peach types and offspring cultivars all revealed prevalent floral, fruity and caramel notes, whereas the higher odor activity values and especially the woody odors in the white-fleshed cultivars, as well as the differential balance degrees of the main odor directions defined the distinct aromas. By delving into the pivotal differences in odor directions and aroma profiles between the two types of peach, this research elucidates the aroma distinctions rooted in flesh color variations and paves the way for uncovering aroma formation mechanisms in fruits with varied flesh colors.